Pelaksanaan Metode Talaqqi dalam Memperbaiki Pengucapan Huruf Halaq (Tenggorokan) pada Pembelajaran Al-Qurán di Rumah Tahfidz Baitul Qurán Kota Padang - Hidayanti, Yesi; Muliati, Indah (ANWARUL, 2024)
This research is motivated by the large number of Tahsin Al-Qurán students who are spread across various places of Al-Qurán education but still have minimal correct pronunciation of Tajweed. This is influenced by learning methods, the role of the teacher, and the regulations set by the Al-Qurán education place. So here it is interesting for me to study the method used in learning Tahsin Al-Qurán, namely the Talaqqi method. What I studied was aimed at finding out the implementation of the students' Halaq letter recitation in the house of the Baitul Qurán tahfidz in Padang City. This study uses a qualitative method. The population of this study was 4 people. Data collection techniques were carried out through observation, interviews and documentation with the head of the Tahfizh House, teachers and students. Data analysis uses data reduction, data presentation, and drawing conclusions. Based on the research results obtained through observations, interviews and documentation at the Baitul Qurán tahfizh house in Padang City, the implementation of the Talaqqi method in correcting the makharijul of Halaq letters at the Baitul Qurán tahfizh house in Padang City is done by the teacher first correcting each of the students' halaq letters, supported by talaqqi book, jaw chart, and blackboard.